General Practice Registrars' Management of and Specialist Referral Patterns for Atopic Dermatitis - Anneliese Willems; Amanda Tapley; Alison Fielding; Vivian Tng; Elizabeth Holliday; Mieke van Driel; Jean Ball; Andrew Davey; Kristen FitzGerald; Neil A. Spike; Parker J. Magin (Mattioli1885, 2021)
Background: Atopic dermatitis (AD) is a common presentation in the general practice (GP) setting. Implementation of appropriate referral pathways is instrumental for best patient care and is an essential skill for Australian GP registrars. Objectives: We aimed to explore the prevalence and associations of GP registrar referrals to specialists for AD management. Methods: A cross-sectional analysis utilizing data from the Registrar Clinical Encounters in Training (ReCEnT) project, an ongoing cohort study that documents in-consultation clinical and educational experience of Australian GP registrars. Registrar, patient, and consultation factors associated with referrals for AD were established using logistic regression. Results: A A total of 3,285 (0.55%) of 595,412 diagnoses managed were AD, of which 222 (6.8%) resulted in referral. Of these referrals, 70% were to dermatologists, 17% to allergists/immunologists, and 10% to pediatricians. Associations of referral included registrar female gender, patient age, longer consultation duration; an established (rather than new) AD diagnosis; supervisor advice being sought; and learning goals being generated.  Conclusions: Both registrar and patient factors influence AD referral patterns. Registrars referred established rather than newly diagnosed AD, suggesting a level of comfort in initial management. Referral was associated with longer consultations, seeking supervisor advice, and generation of learning goals-suggesting these are more complex presentations and, possibly, registrar learning opportunities. A significant proportion of referrals were to non-dermatologist specialists. The implication of this for optimal patient care is a subject for further study.